Influence of the rotation on the natural frequencies of a submerged-confined disk in water. (17th February 2015) - Presas, Alexandre; Valentin, David; Egusquiza, Eduard; Valero, Carme; Seidel, Ulrich
Abstract: In this paper, the effect of the rotation on the natural frequencies and mode shapes of a submerged-confined disk inside a casing with water is studied analytically, numerically and experimentally. To analyze the disk behavior, an analytical model is developed. The model assumes the thin-plate theory for the disk vibration and the Laplace Equation for the velocity potential of the flow on the upper and lower parts of the disk, considering a constant rotating speed of water for each part. A CFD simulation of the flow inside the tank has been performed in order to determine the averaged rotating speed of the water on the upper and lower parts of the disk for different velocities. The averaged rotating speed is introduced in the analytical model and in a FEM numerical model of the test rig. For the experimental investigation a test rig has been developed. It consists of a disk rotating inside a casing filled with water; the rotating speed can be varied from 0 to 8 Hz. The disk is made of stainless steel having a diameter of 400 mm and a thickness of 8 mm. The radial gap between the disk and the casing is of 7 mm, and the axial gap between the disk surface and the upper cover is 10 mm. For the excitation, four piezoelectric patches attached on the disk have been used. In order to measure the response miniature accelerometers are placed on the disk surface at several locations. Signals are transmitted from the rotating to the stationary system through a slip ring located at the tip of the shaft. Natural frequencies and mode shapes of the rotating disk are obtained experimentally for several rotating speeds. These results are discussed in detail and compared with those ones obtained with the analytical model and numerical simulation. The influence of the rotation of the surrounding water with respect to the disk is determined in this paper. Highlights: The effect of rotation on the natural frequencies of a confined and submerged disk in water is studied. Disk is excited (with a piezoelectric patch) and its response measured from the rotating system experimentally. Natural frequencies and mode shapes of the rotating disk in water are discussed in detail. An analytical model to predict the natural frequencies of a totally confined and submerged rotating disk in water is presented. To determine the rotating speed of the flow a CFD calculation has been performed. This parameter is used in the analytical and numerical model. Experimental results have been validated with analytical and numerical results.